Reduced patient anxiety as a result of radiation therapist-led psychosocial support: a systematic review - Elsner, K.; Naehrig, D.; Halkett, Georgia; Dhillon, H. (John Wiley & Sons, 2017)
Up to 49% of patients attending radiation therapy appointments may experience anxiety and distress. Anxiety is heightened during the first few visits to radiation oncology. Radiation therapists (RT) are the only health professionals in direct daily contact with patients during treatment, placing them in a unique position to explore patients’ psychosocial needs. This review aims to synthesise literature regarding the effect of RT-led psychosocial support on patient anxiety. In May 2015, we searched the following electronic databases: Medline, PsycINFO, Embase, CINAHL, PubMed and Cochrane library. Radiation therapy-specific journals were hand-searched, and reference lists of identified studies searched. This review complies with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. The search identified 263 articles, of which 251 were excluded based on non-English language, duplicate article or relevance. A total of 12 articles involving 1363 patients were included and categorised into three broad themes: ‘Patient Perspectives’ 3 articles, ‘Patient Information and Education’ 5 articles and ‘Screening and Needs Assessment’ 4 articles. Two publications referred to the same sample and data. Quality ratings were mixed, with one study rated ‘high’ quality, seven ‘moderate’ and four ‘low’. Methodological weaknesses were identified in relation to workflow, sample size and responder bias. RTs have a role in psychosocial support through increased communication and information sharing, which can benefit both patients and staff. RT-led practices such as relationship building, patient education sessions and screening and needs assessments are feasible and can reduce anxiety.